A Comparative Legal Study on the Regulation of Torts in Indonesia and Singapore - Kristian Zebua, Johan; Zevanya Paparang, Joel; Gibran Joesoef, Paolo; Samuel Tumondanh Bakara, Kenzie; Aditya, Rifaldo (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to compare the regulation of unlawful acts in the legal systems of Indonesia and Singapore. Indonesia applies the concept of onrechtmatige daad derived from Dutch civil law and regulated in Articles 1365–1380 of the Civil Code, while Singapore adopts the common law system inherited from England that places torts as the basis of civil liability. This study uses a normative-comparative approach by examining the laws and regulations, doctrines, and court decisions of both countries. The analysis results show fundamental differences related to the elements, scope, and proof of unlawful acts. The Indonesian system provides more room for judicial interpretation by expanding the definition of unlawful acts, while Singapore uses a more structured classification of torts, such as negligence, nuisance, and defamation. The differences in legal systems have implications for legal protection for the community and the effectiveness of civil law enforcement. This research is expected to contribute to the development of comparative legal studies and national civil law reform.